Laboratory quality management system fundamentals - Pillai, Segaran P.; Fox, Elizabeth (Frontiers in Bioengineering and Biotechnology, 2025)
A laboratory quality management system (LQMS) enables the effective operation of laboratories of all types and sizes. With rapid advances in technology (e.g., artificial intelligence and machine learning, advanced manufacturing) comes the need for laboratories worldwide to conduct proper change management and process improvement to meet the continued demand amidst major changes. In order to do so while ensuring that results and data are accurate, timely, and reproducible, it is crucial for laboratories to sustain a foundational LQMS that accommodates laboratory processes, document and records management, and a path for continual improvement in the laboratory itself and within its contextual organization. A foundational LQMS provides a framework to address gaps in process or product performance and risks present throughout the laboratory’s workflow, any of which could lead to a critical error that compromises the organization’s credibility. There are many LQMS frameworks–benchmarks such as consensus standards or regulations (e.g., Good Laboratory Practices for Nonclinical Laboratory Studies) – that the laboratory can select from to govern its LQMS. While these frameworks vary in applicability, there are several common elements across these frameworks that can serve as the basic components of any LQMS. The aim of this study is to review and assess 12 widely-recognized, fundamental aspects of an LQMS to identify actionable examples and templates that can enable effective implementation of a robust LQMS. A robust LQMS is one that fosters long term success of the laboratory, and which ultimately ensures reliable results, efficient operations, and the protection of public health.